Expatriation of Nepalese Doctors: Is it an Alarming Issue? - Dhungana, Sahadeb Prasad (Journal of Nobel Medical College, 2024)
Nepal, a country nestled in the lap of the Himalayas, is grappling with a troubling phenomenon—the increasing expatriation of its medical doctors. This trend, while not unique to Nepal, raises significant concerns about the situation of the nation’s healthcare system and its ability to provide equitable services to its citizens. Is this migration merely a symptom of global mobility, or is it an alarming issue demanding immediate attention?